2020
DOI: 10.2174/1570159x18666200309101750
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disturbances and Cognitive Impairment in the Course of Type 2 Diabetes-A Possible Link

Abstract: : There is increasing number of the patients worldwide with sleep disturbances and diabetes. Various sleep disorders, including long or short sleep duration and poor sleep quality of numerous causes, may increase the risk of diabetes. Some symptoms of diabetes, such as painful peripheral neuropathy and nocturia, or associated other sleep disorders, such as sleep breathing disorders or sleep movement disorders, may influence the sleep quality and quantity. Both sleep disorders and diabetes may lead to cognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 182 publications
(145 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, short and long sleep duration interferes with the circadian rhythm. Long‐term sleep disorders might cause changes in neuroendocrine function and metabolism, resulting in obesity and insulin resistance, and finally inducing diabetes 78 , 79 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, short and long sleep duration interferes with the circadian rhythm. Long‐term sleep disorders might cause changes in neuroendocrine function and metabolism, resulting in obesity and insulin resistance, and finally inducing diabetes 78 , 79 .…”
Section: Discussionmentioning
confidence: 99%
“…All lifestyle information was self-reported at baseline. In our study, we considered seven low-risk behaviours recommended in diabetes management guidelines 5 and ever used in previous studies, [10][11][12]15,16 including smoking, physical activity, social connection, alcohol consumption, sedentary behaviour, sleep duration and diet, to generate an overall lifestyle score. Definitions and field IDs of each lifestyle factor were listed (Table S2).…”
Section: Assessment Of Type 2 Diabetes and Lifestyle Factorsmentioning
confidence: 99%
“…10 However, the impact of healthy lifestyles on risk of subsequent dementia is less well studied in patients with T2DM. Research has suggested that in people with diabetes, engagement in social leisure activities, 11 regular physical activity [12][13][14] and cohabitation status 15 could reduce the risk of dementia, and sleep disturbance, 16 may increase the risk; however, smoking and alcohol consumption had no clear relationship with dementia. [17][18][19] Previous studies usually analysed the role of a single lifestyle factor on risk of dementia in people with T2DM.…”
mentioning
confidence: 99%
“…Professor Aliev possessed an encyclopedic knowledge in a wide range of scientific fields; however, his main research focus was linked to the development of unique technologies and treatment protocols for age-associated diseases. He was recognized internationally for his work in the fields of gerontology [ 1 , 2 , 3 , 4 , 5 ], oncology [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ], cardiovascular diseases [ 16 , 17 , 18 , 19 ], endocrinology [ 2 , 20 , 21 ], and neurodegenerative diseases [ 15 , 20 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. His research publications on the role of vascular and mitochondrial factors in the pathogenesis of aging [ 2 , 3 , 5 ], atherosclerosis [ 33 , 34 ], ischemia-reperfusion [ 18 , 35 , 36 , 37 ], stroke [ 4 , 18 , 35 , 38 ], and Alzheimer’s disease (AD) [ 23 , 24 , 33 ,…”
mentioning
confidence: 99%
“…Following this, Gjumrakch received postdoctoral training under the prestigious British Heart Foundation Grant Program in the University College London (advisor Professor Geoffrey Burnstock), specializing in medicine.Professor Aliev possessed an encyclopedic knowledge in a wide range of scientific fields; however, his main research focus was linked to the development of unique technologies and treatment protocols for age-associated diseases. He was recognized internationally for his work in the fields of gerontology[1][2][3][4][5], oncology[6][7][8][9][10][11][12][13][14][15], cardiovascular diseases[16][17][18][19], endocrinology[2,20,21], and neurodegenerative diseases[15,20,[22][23][24][25][26][27][28][29][30][31][32]. His research publications on the role of vascular and mitochondrial factors in the pathogenesis of aging[2,3,5], atherosclerosis[33,34], ischemia-reperfusion[18,[35][36][37], stroke…”
mentioning
confidence: 99%